Analisis Yuridis Tindak Pidana Pelecehan Seksual Terhadap Anak Sebagai Korban Ditinjau dari UndangUndang Nomor 35 Tahun 2014 Tentang Perubahan atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak (Studi Putusan Nomor 6/PID/SUS-ANAK/2024/PNJKT - Matondang, Mulia Hamonangan; Nachrawi, Gunawan (Postulat, 2025)
The principle of NEMO IUDEX IN CAUSA SUA is the principle that "no one may be a judge in their own case". Judges are prohibited from handling cases that have a very close relationship with them or their families. The use of this principle, which is related to Article 17 of Law No. 48 of 2009 concerning Judicial Power, is very important to implement so that the purpose of the Constitutional Court trial itself truly achieves its goal, namely preventing judges from taking sides in carrying out their duties in order to obtain decisions that truly have a value of justice for the disputing parties. This principle is certainly very much needed in the trial because the nature of the Constitutional Court's decision is final and binding, which means that the decision immediately has permanent legal force and no other legal remedies can be taken. Regarding the Constitutional Court's decision Number 90/PUU-XXI/2023 which challenges the requirement for presidential and vice presidential candidates to be at least 40 years old according to Law Number 7 of 2017 concerning General Elections, it is very clear that this principle is not applied. The proof is that the judge who was in court and even became the chief judge of the trial was directly involved in handling and even deciding this case. As is known, the one who benefits from this decision is the nephew of the chief justice himself. After this decision was issued, there were many pros and cons among the public. Public reactions were varied. Not a few people and legal experts strongly rejected this decision. The next problem after this decision was how the credibility of the Constitutional Court institution as a seeker of justice in this country. Public trust also faded and became pessimistic. The institution that the public had hoped for turned out to side with the authorities. It did not carry out its function as an independent supervisor in balancing power. In fact, this institution has become a judicial institution that carries out the will of the legislative and executive institutions.